Irrigation--Its relation to the development of the western plains - Painter, William H. (My University, 1895)
Introduction: It is a law of nature that man shall adapt himself to his surroundings. What may prove his best means of gaining a livelihood in one section of a country may be wholly unsuited to another. Methods of agriculture successful in Florida or Louisiana are practically useless to the farmer in New York. No more are Illinois methods suited to the plains of Kansas, Nebraska and Oklahoma. Practical experience has proved that to make it possible for any considerable number of people, more than the present population, to produce enough to live upon between the 98th meridian and the Rocky Mountains some other than the present system of farming must be adopted. The country has been settled by people bred to eastern customs—men fitted for successful farmers in the humid climate of their native state, but practically helpless when thrown under the changed conditions of the semi-arid west. Ten to fifteen years have elapsed since the actual settlement of the broad strip of land of which this article presumes to treat. Many took up land in it merely for speculative purposes but the great majority were home seekers.
Citation: Painter, William H. Irrigation--Its relation to the development of the western plains. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Agriculture; Semi-arid west; Theses; Manuscripts (documents)